The Influence of Biological Sex on Perceived Aggressive Communication in Debater–Judge Conflicts in Parliamentary Debate. Issue 1 (1st January 2016) - Matthews, Nicholas C.
Abstract : This study examines how college debate judges' perceptions of debaters' argumentativeness and verbal aggressiveness are influenced by biological sex in the "reason for decision" stage of parliamentary debates. Debate judges in each of four experimental conditions viewed a video that manipulated the sex of the actor and the amount of verbal aggressiveness used by the actor to express disagreement after a fictional debate round. The results suggest that debate judges perceive female debaters as significantly more verbally aggressive than male debaters in reasons for decisions.